First Records of the Epizoic Barnacle Octolasmis Bullata (Cirripedia: Thoracica: Poecilasmatidae) on the Swimming Crab Portunus Sanguinolentus (Decapoda: Portunidae). Issue 1 (1st January 2014) - Li, Heng-Xiang; Ma, Li-Sha; Yan, Yan; Yang, Chang-Ping; Lin, Chuan-Xu
Abstract: This is the first report of the usually lobster-inhabiting epizoic barnacle Octolasmis bullata (Aurivillius, 1894 ) from the branchial chambers of a crab, Portunus sanguinolentus (Herbst, 1783 ). This association was noted in Hailing Bay, P.R. China, where infestation rates were as high as 34.8% with a mean intensity of 25.44 ± 17.89 (mean ± S.D.) barnacles per infested host. The maximum number was 102 individuals of O. bullata on a single female crab. Prevalence and mean intensity of infestation did not differ between crab sexes, but did differ significantly between immature and mature crabs and among crabs in different molt stages. Larger crabs showed a higher prevalence and mean intensity of barnacle infestation, as has been reported in previous studies of Octolasmis . More than 80% of the barnacles were distributed on the inner surfaces of the gills. The largest number appeared on gill 6, but barnacles were completely absent from gill 1. This species appeared to be more highly host specific than certain other species of Octolasmis, but its spatial distribution on P. sanguinolentus was similar to the patterns shown by some of its crab-inhabiting congeners.